THE EFFECT OF FOREIGN DIRECT INVESTMENT, INFLATION, AND EXPORT ON ECONOMIC GROWTH IN INDONESIAN - Rizki Annisa Fitri (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2022)
A nation's economic health can be gauged by looking at factors like its rate of economic growth. The goal of this research was to identify both long- and short-term relationships among factors that influence economic growth in Indonesia. The period between 1988 and 2017 was used for analysis. In this case, the Error Correction Model is employed (ECM). This research shows that PMA has a positive and statistically insignificant effect both immediately and over time. Inflation is a major drag on economic growth both in the short and long term. To be sure, the export variable has a negative effect in the short term, but in the long run, it has a positive and insignificant effect.